Phosphorus uptake mechanisms associated with phosphorus application levels in two cotton cultivars - Cai, Fangyuan; Zhang, Yingrong; Hou, Tianyu; Zhang, Man; Wang, Juanhong; Chen, Bolang (Frontiers in Environmental Science, 2023)
Poor phosphorus utilization is a common limitation of sustainable cotton production. Even so, the intrinsic potential for efficient phosphorus acquisition of the root remains unclear. In this study, we aimed to explore if phosphorus acquisition in cotton could be affected by the interactions, which could possibly be associated with root morphology and gene expression, between genotype and application rates. A pot experiment was conducted with seven phosphorus application rates, i.e. 0, 12.5, 25, 50, 75, 150, and 300 mg P kg -1 . The agronomic characters, root morphology, and the expression of the PHT1 gene in the roots with different phosphorus efficiency varieties were measured. According to the results, The Phosphorus-efficiency cultivar XLZ19 had a higher phosphorus uptake than XLZ13 due to upregulating the expression of the GhPTs gene, increasing the total root length and the proportion of fine roots. Olsen-P levels in the soil ranged from 20 to 30 mg kg -1 at the seedling stage and from 15 to 25 mg kg -1 at the flowering stage, suggesting better root growth and phosphorus supply. Phosphorus fertilizers that convert into soil Olsen-P decreased when the phosphorus application rate exceeded 50-75 mg kg -1 . The phosphorus-efficient XLZ19 phenotype owes its efficiency to high GhPTs expression and morphological changes in the roots. Finally, with these crop that are highly efficient in phosphorus acquisition, agricultural practices may consume less phosphorus fertilizers.